School Principals’ Self-Identity According to The Perspective of Transpersonal Psychology - Mundiri, Akmal; Manshur, Umar (IAIN Ponorogo, 2020)
Abstract: The school principal at the pesantren, displays a unique self-image that distinguishes itself from the others. In the school principal's self-identity is attached to the appreciation of values that become the core beliefs and core values of the principal. This study uses a qualitative approach to the type of phenomenology. Thus, this study seeks to explore the phenomenon of identity formation or forms of identity in the perspective of transpersonal psychology. The results of this study indicate that the formation of principals-based principals' self-identity is carried out in the form of self-understanding, parenting style and role models. Whereas the principal's identity pattern based on pesantren in the perspective of transpersonal psychology at pondok pesantren Nurul Jadid is in the form of spiritual awareness and ability to manage the ego (trans-ego). Thus, this study generally describes findings of self-identity oriented to the nafsani substance in the form of integration of three forces, namely; the heart (fitrah ilahiyah) as a superconscious aspect that has emotional power; reason (fitrah insaniyah) as an aspect of consciousness that has the power of cognition; and lust (fitrah hayawaniah) as an aspect of the pre or unconscious that has the power of konasi.Â Ø§Ù„Ù…Ù„Ø®Øµ: ÙŠØ¹Ø±Ø¶ Ø§Ù„Ù…Ø¯ÙŠØ±Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…Ø¹Ù‡Ø¯ÙŠØ© ØµÙˆØ±Ø© Ø°Ø§ØªÙŠØ© ÙØ±ÙŠØ¯Ø© ØªÙ…ÙŠØ² Ù†ÙØ³Ù‡Ø§ Ø¹Ù† Ø§Ù„Ø¢Ø®Ø±ÙŠÙ†. ÙÙŠ Ø§Ù„Ù‡ÙˆÙŠØ© Ø§Ù„Ø°Ø§ØªÙŠØ© Ø§Ù„ÙƒØ§Ù…Ù†Ø© Ù‡Ù†Ø§Ùƒ ØªÙ‚Ø¯ÙŠØ± Ù„Ù„Ù‚ÙŠÙ… Ø§Ù„ØªÙŠ Ø¨Ø¯ÙˆØ±Ù‡Ø§ ØªØµØ¨Ø Ø§Ù„Ù…Ø¹ØªÙ‚Ø¯Ø§Øª Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© ÙˆØ§Ù„Ù‚ÙŠÙ… Ø§Ù„Ø£Ø³Ø§Ø³ÙŠØ© Ù„Ù„Ù…Ø¯ÙŠØ±. ØªØ³ØªØ®Ø¯Ù… Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù†Ù‡Ø¬Ù‹Ø§ Ù†ÙˆØ¹ÙŠÙ‹Ø§ Ù„Ù†ÙˆØ¹ fenomenologi. ÙˆØ¨Ø§Ù„ØªØ§Ù„ÙŠ ØŒ ØªØ³Ø¹Ù‰ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ø§Ø³ØªÙƒØ´Ø§Ù Ø¸Ø§Ù‡Ø±Ø© ØªÙƒÙˆÙŠÙ† Ø§Ù„Ù‡ÙˆÙŠØ© Ø£Ùˆ Ø£Ø´ÙƒØ§Ù„ Ø§Ù„Ù‡ÙˆÙŠØ© ÙÙŠ Ù…Ù†Ø¸ÙˆØ± Ø¹Ù„Ù… Ø§Ù„Ù†ÙØ³ Ø¹Ø¨Ø± Ø§Ù„Ø´Ø®ØµÙŠØ©. ØªØ´ÙŠØ± Ù†ØªØ§Ø¦Ø¬ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø¥Ù„Ù‰ Ø£Ù† ØªØ´ÙƒÙŠÙ„ Ø§Ù„Ù‡ÙˆÙŠØ© Ø§Ù„Ø°Ø§ØªÙŠØ© Ù„Ù„Ù…Ø¯ÙŠØ±ÙŠÙ† Ø§Ù„Ø°ÙŠÙ† ÙŠØ¹ØªÙ…Ø¯ÙˆÙ† Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø¨Ø§Ø¯Ø¦ ÙŠØªÙ… ÙÙŠ Ø´ÙƒÙ„ ÙÙ‡Ù… Ø§Ù„Ø°Ø§Øª ØŒ ÙˆØ£Ø³Ù„ÙˆØ¨ Ø§Ù„ÙˆØ§Ù„Ø¯ÙŠØ© ÙˆÙ†Ù…Ø§Ø°Ø¬ Ø§Ù„Ù‚Ø¯ÙˆØ©. Ùˆ Ø£Ù† Ù†Ù…Ø· Ù‡ÙˆÙŠØ© Ø§Ù„Ù…Ø¯ÙŠØ± Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ù…Ù†Ø¸ÙˆØ± Ø¹Ù„Ù… Ø§Ù„Ù†ÙØ³ Ø¹Ø¨Ø± Ø§Ù„Ø´Ø®ØµÙŠØ© ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ù†ÙˆØ± Ø§Ù„Ø¬Ø¯ÙŠØ¯ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙŠ Ø´ÙƒÙ„ Ø§Ù„ÙˆØ¹ÙŠ Ø§Ù„Ø±ÙˆØÙŠ ÙˆØ§Ù„Ù‚Ø¯Ø±Ø© Ø¹Ù„Ù‰ Ø¥Ø¯Ø§Ø±Ø© Ø§Ù„Ø£Ù†Ø§ (trans-ego). Ù‡ÙƒØ°Ø§ ØŒ ÙŠØµÙ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¨Ø´ÙƒÙ„ Ø¹Ø§Ù… Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ù‡ÙˆÙŠØ© Ø§Ù„Ø°Ø§ØªÙŠØ© Ø§Ù„Ù…ÙˆØ¬Ù‡Ø© Ø¥Ù„Ù‰ Ù…Ø§Ø¯Ø© Ø§Ù„Ù†ÙØ³Ø§Ù†ÙŠ ÙÙŠ Ø´ÙƒÙ„ ØªÙƒØ§Ù…Ù„ Ù‚ÙˆØ© Ø§Ù„Ø«Ù„Ø§Ø«Ø© ØŒ ÙˆÙ‡ÙŠ: Ø§Ù„Ù‚Ù„Ø¨ (ÙØ·Ø±Ø© Ø§Ù„Ø¯ÙŠÙˆØ§Ù†ÙŠØ©) Ø¨Ø§Ø¹ØªØ¨Ø§Ø±Ù‡ Ø¬Ø§Ù†Ø¨Ù‹Ø§ ÙØ§Ø¦Ù‚ Ø§Ù„ÙˆØ¹ÙŠ Ù„Ù‡ Ù‚ÙˆØ© Ø¹Ø§Ø·ÙÙŠØ© (Ø§Ù„Ø°ÙˆÙ‚) Ø› Ø§Ù„Ø¹Ù‚Ù„ (ÙØ·Ø±Ø© Ø§Ù„Ø¬Ù†Ø§Ù†ÙŠØ©) Ø¨Ø§Ø¹ØªØ¨Ø§Ø±Ù‡ Ø¬Ø§Ù†Ø¨Ø§ Ù…Ù† Ø§Ù„ÙˆØ¹ÙŠ Ø§Ù„Ø°ÙŠ Ù„Ù‡ Ù‚ÙˆØ© Ø§Ù„Ø¥Ø¯Ø±Ø§Ùƒ (ØÙ‚ÙˆÙ‚ Ø§Ù„Ù†Ø´Ø±) Ø› ÙˆØ§Ù„Ø´Ù‡ÙˆØ© (ÙØ·Ø±Ø© ØÙŠØ§ÙˆÙ†ÙŠØ©) Ø¨Ø§Ø¹ØªØ¨Ø§Ø±Ù‡Ø§ Ø¬Ø§Ù†Ø¨Ù‹Ø§ Ù…Ù† Ø§Ù„Ù„Ø§ÙˆØ¹ÙŠ Ø£Ùˆ Ø§Ù„Ù„Ø§ÙˆØ¹ÙŠ Ø§Ù„Ø°ÙŠ Ù„Ø¯ÙŠÙ‡ Ù‚ÙˆØ© ÙƒÙˆÙ†Ø§Ø³ÙŠ (karsa).Â Abstrak: Kepala sekolah di pesantren menampilkan citra diri yang unik yang membedakan dirinya dengan yang lain. Dalam identitas diri kepala sekolah melekat suatu penghayatan nilai yang menjadi core belief dan core values pribadi kepala sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan jenis fenomenologi. Dengan demikian, penelitian ini berupaya menggali fenomena pembentukan identitas ataupun bentuk identitas dalam perspektif psikologi transpersonal. Hasil penelitian ini menunjukkan bahwa pembentukan identitas diri kepala sekolah berbasis pesantren dilakukan dalam bentuk self understanding, parenting style dan model figur panutan. Sedangkan pola identitas diri kepala sekolah berbasis pesantren dalam perspektif psikologi transpersonal di pondok pesantren Nurul Jadid berupa kesadaran spiritual dan kemampuan dalam mengelola ego (trans-ego). Penelitian ini secara umum menggambarkan temuan identitas diri yang berorientasi pada substansi nafsani yang berupa integrasi tiga daya, yaitu; kalbu (fitrah ilahiyah) sebagai aspek supra-kesadaran yang memiliki daya emosi (rasa); akal (fitrah insaniyah) sebagai aspek kesadaran yang memiliki daya kognisi (cipta); dan nafsu (fitrah hayawaniah) sebagai aspek pra atau bawah-sadar yang memiliki daya konasi (karsa).